2022
DOI: 10.3390/su142316236
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Climate Change Impacts on Agricultural Water Availability in Cimanuk Watershed, Indonesia

Abstract: Climate change has been affecting agricultural water resources dynamics spatially and temporally. This article presents analysis results of climate change impact on agricultural water availability in Cimanuk Watershed, Indonesia. STREAM was utilized to model agricultural water availability through FAO MOSAICC web application. Climate spatial data time-series were generated using 3 Global Climate Model (GCM), i.e.,: CanESM2, CNRM-CM5, and MPI-ESM-MR following two climate change scenarios of RCP4.5 and 8.5. Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Farmers' knowledge coupled with the actual data analysis may concertedly give a clearer understanding of climate change-related instability and patterns in weather variables, which is critically important for planning and implementing appropriate adaptation measures in their farming against climate change in the Kashmir Valley [17]. The results showed a decreasing volumetric water availability from all generated climate data and scenarios, identified by comparing the discharge normal distribution of the historical and future data periods [10]. CHIRPS proved to be an effective alternative tool for deriving spatio-temporal trends of drought using two important hydrometeorological indices, viz., Rainfall Anomaly Index (RAI) and Standardized Precipitation Index (SPI).…”
Section: Introductionmentioning
confidence: 97%
“…Farmers' knowledge coupled with the actual data analysis may concertedly give a clearer understanding of climate change-related instability and patterns in weather variables, which is critically important for planning and implementing appropriate adaptation measures in their farming against climate change in the Kashmir Valley [17]. The results showed a decreasing volumetric water availability from all generated climate data and scenarios, identified by comparing the discharge normal distribution of the historical and future data periods [10]. CHIRPS proved to be an effective alternative tool for deriving spatio-temporal trends of drought using two important hydrometeorological indices, viz., Rainfall Anomaly Index (RAI) and Standardized Precipitation Index (SPI).…”
Section: Introductionmentioning
confidence: 97%
“…Another case study about the correlation between irrigation and climate change's adaptation strategy was conducted in Southern Italy by [22], stating that irrigation networks' susceptibility to climate change conditions and water loss will rise in the absence of effective water management and distribution systems. A study by [23] used the STREAM approach to analyze the effects of climate change and the availability of agricultural water in the Cimanuk watershed; the findings indicated that the agriculture water balance within the Cimanuk Watershed was in critical condition. Poor infrastructure was one of the reasons for vulnerability in the Hindu Kush Himalayan area, specifically susceptible to climate change [24].…”
Section: Introductionmentioning
confidence: 99%